1986
DOI: 10.1128/mcb.6.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence of the mouse skeletal alpha-actin gene reveals several conserved and inverted repeat sequences outside of the protein-coding region.

Abstract: The complete nucleotide sequence of a genomic clone encoding the mouse skeletal a-actin gene has been determined. This single-copy gene codes for a protein identical in primary sequence to the rabbit skeletal a-actin. It has a large intron in the 5'-untranslated region 12 nucleotides upstream from the initiator ATG and five small introns in the coding region at codons specifying amino acids 41/42, 150, 204, 267, and 327/328. These intron positions are identical to those for the corresponding genes of chickens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 33 publications
0
48
1
Order By: Relevance
“…The GPD probe was a 0.9 kb EcoRI fragment of pL10.9 (28). The actin probe was a 6.8 kb EcoRI fragment ofpSP62-PL (15). With the use of this a-actin DNA, /3-actin mRNA was detected by RNAblot analysis to check the total amount of RNAloaded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPD probe was a 0.9 kb EcoRI fragment of pL10.9 (28). The actin probe was a 6.8 kb EcoRI fragment ofpSP62-PL (15). With the use of this a-actin DNA, /3-actin mRNA was detected by RNAblot analysis to check the total amount of RNAloaded.…”
Section: Methodsmentioning
confidence: 99%
“…RNAwas prepared from cultured cells by homogenization in guanidinium isothiocyanate, followed by centrifugation over a cesium chloride cushion (5). The RNAwas then electrophoresed in a 1.0% agarose gel, transferred to a nylon filter (Du Pont Company NENProducts), and hybridized with CDNAinserts labeled with 32P-dCTP by the random-primer method (9) at 65°C for [14][15][16] hours in buffer containing 5xSSPE…”
Section: Methodsmentioning
confidence: 99%
“…The MAPF footprint occurs within a dyad symmetry element that is conserved in the actin genes (22,32,33,47). These sequences are found in muscle and nonmuscle genes, and they have been collectively referred to as "CArG boxes" (29).…”
mentioning
confidence: 99%
“…Comparison of nucleotide sequences within these regulatory regions revealed stretches of several conserved motifs shared by many of these myogenic cell-specified genes (25,34,44,50). However, no common sequence has been identified that coordinates the transcriptional activation of all myogenic cell-regulated genes.…”
mentioning
confidence: 99%